2023
DOI: 10.3390/ijms241411238
|View full text |Cite
|
Sign up to set email alerts
|

Transition Networks Unveil Disorder-to-Order Transformations in Aβ Caused by Glycosaminoglycans or Lipids

Abstract: The aggregation of amyloid-β (Aβ) peptides, particularly of Aβ1−42, has been linked to the pathogenesis of Alzheimer’s disease. In this study, we focus on the conformational change of Aβ1−42 in the presence of glycosaminoglycans (GAGs) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) lipids using molecular dynamics simulations. We analyze the conformational changes that occur in Aβ by extracting the key structural features that are then used to generate transition networks. Using the same three feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Given the abundance of Zn 2+ in Aβ aggregated structures, our study highlights the role of Zn 2+ playing in the assembled structure of Aβ 16–22 and gives a clue on modulating the assemble process by the addition of Zn 2+ ions. We note that other metal ions have also shown a similar effect for the disruption of the salt bridge. , Using the same force field CHARMM36m, Strodel et al found that Ca 2+ can bind to Glu22 of Aβ 16–22 and inhibit peptide aggregation by disrupting the Lys16-Glu22 salt bridge . Another study on the full-length Aβ showed that Na + aggregate near Glu22 and Asp23, thus screening the electrostatic interaction between Glu22/Asp23 and Lys28 .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Given the abundance of Zn 2+ in Aβ aggregated structures, our study highlights the role of Zn 2+ playing in the assembled structure of Aβ 16–22 and gives a clue on modulating the assemble process by the addition of Zn 2+ ions. We note that other metal ions have also shown a similar effect for the disruption of the salt bridge. , Using the same force field CHARMM36m, Strodel et al found that Ca 2+ can bind to Glu22 of Aβ 16–22 and inhibit peptide aggregation by disrupting the Lys16-Glu22 salt bridge . Another study on the full-length Aβ showed that Na + aggregate near Glu22 and Asp23, thus screening the electrostatic interaction between Glu22/Asp23 and Lys28 .…”
Section: Discussionmentioning
confidence: 62%
“…46 Another study on the full-length Aβ showed that Na + aggregate near Glu22 and Asp23, thus screening the electrostatic interaction between Glu22/Asp23 and Lys28. 49 Taken together, this suggests that the disruptive effect of cations on salt bridges may be a common occurrence in biomolecules.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To understand what the problem is and whether there are force fields capable of reliably modeling the intrinsic disorder of peptides such as $$ \mathrm{A}\upbeta $$ while also modeling their folding, either through interaction with other molecules or through self‐interactions leading to amyloid aggregation, she and her team performed several force field benchmark tests for both monomeric $$ \mathrm{A}\upbeta $$ 194,195 and for amyloid aggregation 196–198 . This work has largely benefited from the work of others who have developed force fields better suited for IDPs, 199,200 and the current conclusion of the Strodel group is that Charmm36m 200 provides the best balance between representing the fully unfolded state of $$ \mathrm{A}\upbeta $$, 195 modeling it is folding into α‐helical or β‐sheet structures in molecular interactions, 201,202 and reproducing kinetic and thermodynamic aspects of amyloid aggregation 196 …”
Section: Review Of Simulation Studies On Amyloid Aggregationmentioning
confidence: 99%